Multimodal-Based Approaches in Teaching Ecological Literacy: Enhancing Environmental Awareness through Textual, Visual, and Auditory Integration - Bambang Nur Alamsyah Lubis (STAIRS: English Language Education Journal, 2025)
The rise of digital platforms and media has made it essential for educators to adopt innovative methods that appeal to diverse learning styles, thus fostering a deeper connection to ecological concepts. This study explores the use of multimodal-based approaches in teaching ecological literacy, focusing on the integration of textual, visual, and auditory elements to enhance students' understanding of environmental issues. Quantitative and qualitative approach was used in this study, employing a case study method with pre- and post-test assessments to measure students' ecological literacy levels before and after the implementation of multimodal teaching techniques. Data was collected through surveys, interviews, and observation to gather a rich understanding of the students' experiences. The results indicate that the use of multimodal teaching methods significantly enhanced students' ecological literacy, with notable improvements in both cognitive understanding and emotional engagement with environmental issues. Students showed increased awareness and critical thinking skills regarding ecological challenges, and their ability to connect theory with real-world applications was strengthened. In the discussion, it is highlighted that multimodal-based approaches not only improve comprehension but also foster a more inclusive learning environment, allowing students to engage with content in varied and meaningful ways. These findings suggest that multimodal approaches are essential for contemporary ecological education, encouraging both knowledge retention and active participation in environmental advocacy.